Metformin Versus Insulin in The Management of Gestational Diabetes Mellitus - Al-Rubai, Sajida; Fouad , Huda Q.; Muhsen, Nuha (Scientific Journal of Medical Research, 2021)
Background: Insulin and metformin have been used extensively in the management of gestational diabetes mellitus (GDM). Insulin has been the primary medical treatment if maternal glucose targets are not achieved by dietary therapy. Insulin is safe for the fetus because it does not normally cross the placenta. Oral antidiabetic agents, glibenclamide, and metformin are the most studied agents to treat GDM patients. Objective: To examine if oral metformin is as effective as insulin in the prevention of fetal macrosomy in pregnancies complicated with GDM. Method: In this prospective randomized controlled study, 100 women with GDM who did not achieve euglycaemia with dietary regulation were enrolled. Women were randomized to receive either insulin (n=50) or oral metformin (n=50). Incidence of macrosomia in infants and neonatal morbidity was measured. Results: There were no statistically significant differences in the incidence of macrosomia (16% versus 20%), and neonatal morbidity between insulin and metformin groups. Around 15 (30%) of the metformin-treated women needed supplemental insulin. They were more obese, (36.2 versus 30.6) kg/m2 bad higher fasting blood sugar levels (7.4 mmol/L versus 6.1 mmol/L) and required medical therapy for GDM earlier (27 versus 32 weeks) than women who were normoglycemic with metformin only. Higher rate of caesarean sections in the metformin than in the insulin arm. Conclusion: Metformin might prevent fetal macrosomia, especially in lean or overweight women developing GDM in late pregnancy Women with significant obesity, high fasting blood sugar, and an early need for medical treatment may be a candidate for insulin treatment.